Recruitment Process Outsourcing: Eine Szenariostudie zur Akzeptanz von Outsourcing-Maßnahmen im Recruitment. - Giardini, A; Kabst, Rüdiger (Zeitschrift für Personalforschung.)

The Effects of Work-Family HR practices: A Longitudinal Perspective. - Giardini, A; Kabst, R (International Journal of Human Resource Management.)

Effektivität und Effizienz von Anti-Spam-Maßnahmen - Schryen, Guido (Linux Technical Review)

Practical Security of Large-scale Elections: An Exploratory Case Study of Internet Voting in Estonia - Schryen, Guido (7th Workshop on e-Business (WEB 2008, AIS Special Interest Group on E-Business))
The Estonian parliamentary election in 2007 is regarded as a success story of large-scale Internet elections. I use this election in a single case study on practical security to show that low quality of security and its management does not necessarily prevent large-scale Internet elections from being conducted. I also provide research propositions with regard to future challenges for large-scale Internet elections.
Keywords: Internet voting; large-scale election; Estonian parliamen- tary election; security; security management

Einspeiseschwankungen von Offshore-Windparks - kann das Wind-Potential auf dem Meer effizient genutzt werden? - Bendfeld, Jörg; Splett, Michael; Ditscherlein, Ralf; Voss, Jürgen (EnInnov 08 – 10. Symposium Energieinnovation; Energiewende)

Zukunftspotential auf See - Messungen als Grundlage für die Errichtung von Offshore-Windkraftwerken - Bendfeld, Jörg; Splett, Michael; Ditscherlein, Ralf; Voss, Jürgen (EnInnov 08 – 10. Symposium Energieinnovation; Energiewende)

Input Variabillity of spaciours distributed offshore wind farms in the German North Sea - Bendfeld, Jörg; Splett, Michael; Ditscherlein, Ralf; Voss, Jürgen (Proceedings of the European Wind Energy Conference & Exhibition (EWEC 2008))

Possibilities of using reanalysis data for the estimation of wind energy output for offshore wind farms in the German Baltic Sea - Bendfeld, Jörg; Splett, Michael; Ditscherlein, Ralf (Proceedings of the European Wind Energy Conference & Exhibition (EWEC 2008))

The German Offshore Metmasts Amrumbank West and Arkonabecken Südost - Bendfeld, Jörg; Splett, Michael; Ditscherlein, Ralf; Voss, Jürgen (Proceedings of the European Wind Energy Conference & Exhibition (EWEC 2008))

ADCP and Waverider Measurements for O&M at offshore wind farm locations - Bendfeld, Jörg; Splett, Michael; Ditscherlein, Ralf; Voss, Jürgen (Proceedings of the European Wind Energy Conference & Exhibition (EWEC 2008))

Kombinationspotenzial von Offshore-Windkraftwerken und Biogaskraftwerken zur Reduzierung von Einspeisefluktuationen - Bendfeld, Jörg; Tigges, Martin; Splett, Michael; Voss, Jürgen (Proceedings of the World Sustainable Energy Days (WSED 2008))

Analyse und Bewertung eines Akustischen Doppler Strömungsprofilmessgerätes an einem Standort in der Deutschen Bucht - Bendfeld, Jörg; Ditscherlein, Ralf; Voss, Jürgen (Wissenschaftliche Verhandlungen 2008 der Deutschen Physikalischen Gesellschaft, Darmstadt, März 2008)

Input variability of spacious distributed offshore wind farms - Bendfeld, Jörg; Ditscherlein, Ralf; Splett, Michael; Voss, Jürgen (American Wind Energy Association, WINDPOWER 2008 Conference and Exhibition, Houston, Texas, USA, Juni 2008)

Operation and Maintenance for offshore windfarms based on ADCP and Waverider Measurements - Bendfeld, Jörg; Ditscherlein, Ralf; Splett, Michael; Voss, Jürgen (American Wind Energy Association, WINDPOWER 2008 Conference and Exhibition, Houston, Texas, USA, Juni 2008)

Compensation for the Feed-in Fluctuations of Offshore Wind Parks by Biogas Plants - Bendfeld, Jörg; Tigges, Martin; Splett, Michael; Voss, Jürgen (31st IAEE (International Association for Energy Economics) International Conference "Bridging Energy Supply and Demand: Logistics, Competition and Environment", Instanbul, Türkei, Juni 2008)

Analysis and Effects of Offshore Wind Energy Fluctuations - Bendfeld, Jörg; Splett, Michael; Tigges, Martin (31st IAEE (International Association for Energy Economics) International Conference "Bridging Energy Supply and Demand: Logistics, Competition and Environment", Instanbul, Türkei, Juni 2008)

The German Offshore-Metmasts Amrumbank West and Arkonabecken Südost - Bendfeld, Jörg (7th World Wind Energy Conference, WWEC 2008 Kingston, Ontario, Kanada, Juni 2008)

O&M for offshore windfarms based on ADCP and Waverider - Bendfeld, Jörg; Ditscherlein, Ralf; Splett, Michael; Voss, Jürgen (7th World Wind Energy Conference, WWEC 2008 Kingston, Ontario, Kanada, Juni 2008)

Possibilities of Reducing the Feed-In fluctuations of Offshore WindFarms - Bendfeld, Jörg; Splett, Michael; Tigges, Martin (7th World Wind Energy Conference, WWEC 2008 Kingston, Ontario, Kanada, Juni 2008)

Analysis of Fluctuations of Spacious Distributed Offshore Wind farms in Germany - Bendfeld, Jörg; Splett, Michael; Tigges, Martin (7th World Wind Energy Conference, WWEC 2008 Kingston, Ontario, Kanada, Juni 2008)